Needs Analysis for Developing an Islamic Religious Education and Character Curriculum Incorporating Local Wisdom in West Java Senior High Schools - Agus Ruswandi; Hasan Basri; Setia Gumilar; Mahmud Mahmud (CV. AFDIFAL MAJU BERKAH, 2025)
This study aims to analyze the needs for developing the Merdeka Curriculum in the subject of Islamic Religious Education (PAI) and Character, based on local wisdom at the senior high school level, with a focus on the cultural context of West Java communities. The background of this research lies in the predominance of textual and normative approaches in PAI instruction, which have not fully accommodated local values such as religious traditions, regional languages, and living cultural practices within society. Using a mixed-methods approach with a concurrent triangulation design, data were collected through questionnaires and interviews involving 373 students and 191 PAI teachers from five public senior high schools in West Java. The findings indicate that more than 70% of respondents support the integration of local wisdom values into the PAI curriculum. The most prominent aspects include the need for contextual learning guidelines, the scarcity of locally relevant textbooks, and the importance of using regional languages in delivering religious materials. The study concludes that developing a PAI curriculum adaptive to local cultural contexts is not only crucial for enhancing the relevance of learning but also strategic in shaping an inclusive, moderate religious identity rooted in students’ social realities. The results of this needs analysis are expected to serve as both a conceptual and practical foundation for designing a PAI curriculum that is contextual and responsive to the dynamics of Indonesia’s multicultural society.